PENGARUH CORPORATE SOSIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - B41108031, Heny Kusumawati (Jurnal KIAFE, 2013)
The research conducts study is the first aim, of the influence of corporate social responsibility (CSR) on firm value to profitability as a moderating variable. The sample of the study consisted of 40 manufacturing companies listed on the Indonesia Stock Exchange in 2010 and 2011. Researchers obtain data by using purposive sampling and testing hypotheses using the Simple Regression Analysis and Moderated Regression Analysis (MRA). The method of analysis in this study is a simple regression analysis and multiple regression analysis. The results of this study indicate that the disclosure of corporate social responsibility (CSR) have a significant effect on firm value. Profitability as a moderating variable may not affect the relationship disclosure of corporate social responsibility (CSR) and firm value. Keywords: corporate social responsibility (CSR), firm value, profitability